Partial replacement of dietary buffalo meat on the bone with chicken carcass improves serum antioxidant profile of zoo‐housed Indian leopards (Panthera pardus fusca). Issue 3 (5th April 2019) - Sarode, Roshan M.; Das, Asit; Verma, Ashok K.; Singh, Putan; Saini, Mohini; Bhardwaj, Yogesh; Sharma, Anil K.
Abstract: This experiment was conducted to study the effect of gradual replacement of dietary buffalo meat on the bone (BMB) with chicken carcass (CC) on nutrient utilization, serum cortisol, and total serum antioxidant profile of zoo‐housed Indian leopard. Twelve adult leopards were randomly distributed into a replicated Latin square design comprising three treatments, three periods, four animals, and three sequences. Leopards in group T1 were fed normal zoo diet of BMB. On the basis of dry matter, 10% and 20% of BMB was replaced with CC in groups T2 and T3, respectively. Each experimental period comprised 21 days. During each period, a digestion trial of 4‐day collection period was conducted after an adaptation period of 17 days. On Day 21 of each experimental period, blood was collected from all the animals by puncturing the ventral coccygial vein. Intake and apparent digestibility of major nutrients were similar among the groups. Replacement of 20% BMB with addition of CC increased ( p  < 0.001) the calculated supply of I, niacin, and vitamin A. Carotenoid intake increased ( p  < 0.01) with increased level of CC in the diet. Serum concentration of cortisol decreased ( p  < 0.01) whereas serum concentration of total carotenoids increased ( p  < 0.001) with increased level of CC in the diet. Serum concentration of antioxidant enzymes increased ( p  < 0.001) with increased level of CC in the diet. It was concluded that replacement of 20% of BMB with CC increased antioxidant profile. This may reduce oxidative stress in zoo‐housed Indian leopards without any adverse effect on nutrient utilization. HIGHLIGHTS: Replacement of 20% buffalo meat on the bone (BMB) with addition of chicken carcass (CC) increased (P<0.001) the calculated supply of iodine, niacin and vitamin A. Carotenoid intake increased (P<0.01) with increased level of CC in the diet. Serum concentration of cortisol decreased (P<0.01) while serum concentration of total carotenoids (TC) increased (P<0.001) with increased level of CC in the diet. Serum concentration of antioxidant enzymes increased (P<0.001) with increased level of CC in the diet. It was concluded that replacement of 20% of BMB with CC increased antioxidant profile. This may reduce oxidative stress in zoo-housed Indian leopards without any adverse effect on nutrient utilization. Abstract :